2021
DOI: 10.1097/hjh.0000000000002821
|View full text |Cite
|
Sign up to set email alerts
|

Low admission blood pressure as a marker of poor 1-year survival in patients with revascularized critical limb ischemia

Abstract: Objective: To contrast the association between blood pressure (BP) level and antihypertensive medications at hospital admission with 1-year mortality in patients undergoing revascularization for critical limb ischemia (CLI).Methods: From November 2013 to May 2019, 315 consecutive patients were retrospectively included. A median of seven (IQR 3-13) separate readings were recorded for each patient before revascularization procedure and the average represented patient's mean BP. BP-lowering medications, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Another retrospective study examined the impact of BP on mortality in 315 patients with CLI undergoing revascularization and found an inverse relationship with SBP and mortality at 1 year (HR 0.97 [95% CI 0.95–0.99], P = 0.005). Similarly, an inverse relationship was found with mean BP and PP and mortality but not DBP [56 ▪ ]. Finally, another retrospective study of 165 patients undergoing below knee interventions for CLI found no difference in the incidence of mortality, target lesion revascularization, target extremity revascularization, and limb salvage rate, but an increased amputation rate in patients with controlled BP vs. uncontrolled BP defined as >140/90 (33.9 vs. 19.6%, P = 0.045) [57].…”
Section: Post Revascularizationmentioning
confidence: 79%
“…Another retrospective study examined the impact of BP on mortality in 315 patients with CLI undergoing revascularization and found an inverse relationship with SBP and mortality at 1 year (HR 0.97 [95% CI 0.95–0.99], P = 0.005). Similarly, an inverse relationship was found with mean BP and PP and mortality but not DBP [56 ▪ ]. Finally, another retrospective study of 165 patients undergoing below knee interventions for CLI found no difference in the incidence of mortality, target lesion revascularization, target extremity revascularization, and limb salvage rate, but an increased amputation rate in patients with controlled BP vs. uncontrolled BP defined as >140/90 (33.9 vs. 19.6%, P = 0.045) [57].…”
Section: Post Revascularizationmentioning
confidence: 79%